Effects of atmospheric air plasma treatment of graphite and carbon felt electrodes on the anodic current from Shewanella attached cells - Epifanio, Monica; Inguva, Saikumar; Kitching, Michael; Mosnier, Jean-Paul; Marsili, Enrico (Bioelectrochemistry (Amsterdam, Netherlands), 2015)
The attachment of electrochemically active microorganisms (EAM) on an electrode is determined by both the chemistry and topography of the electrode surface. Pre-treatment of the electrode surface by atmospheric air plasma introduces hydrophilic functional groups, thereby increasing cell attachment and electroactivity in short-term experiments. In this study, we use graphite and carbon felt electrodes to grow the model EAM Shewanella loihica PV-4 at oxidative potential (0.2V vs. Ag/AgCl). Cell attachment and electroactivity are measured through electrodynamic methods. Atmospheric air plasma pre-treatment increases cell attachment and current output at graphite electrodes by 25%, while it improves the electroactivity of the carbon felt electrodes by 450%. Air plasma pre-treatment decreased the coulombic efficiency on both carbon felt and graphite electrodes by 60% and 80%, respectively. Microbially produced flavins adsorb preferentially at the graphite electrode, and air plasma pre-treatment results in lower flavin adsorption at both graphite and carbon felt electrodes. Results show that air plasma pre-treatment is a feasible option to increase current output in bioelectrochemical systems. •Air plasma pre-treatment increases Shewanella attachment on carbon felt electrode•Plasma pre-treatment increases current output by 450% at carbon felt electrodes•Coulombic efficiency decreases after plasma pre-treatment for all electrodes•Adsorbed flavins mediate electron transfer at graphite and carbon felt electrodes